Integral Dose-Based Inverse Optimization May Reduce Side Effects in Radiotherapy of Prostate Carcinoma - Mihaylov, Ivaylo B. (Frontiers in Oncology, 2017)
Purpose: The purpose of this work is to apply a novel inverse optimization approach, based on utilization of quantitative imaging information in the optimization function, to prostate carcinoma. Materials and Methods: This new inverse optimization algorithm relies upon quantitative information derived from computed tomography (CT) imaging studies. The Hounsfield numbers of the CT voxels are converted to physical density, which in turn is used to calculate voxel mass and the corresponding integral dose, by summation over the product of dose and mass in each dose voxel. This integral dose is used for plan optimization through its global minimization. The optimization results are compared to the optimization results derived from most commonly used dose-volume-based inverse optimization, where objective functions are formed as summation over all dose voxels of the squared differences between voxel doses and user specified doses. The data from twenty-five prostate plans were optimized with dose-volume (DVH) and integral dose (Energy) minimization objective functions. The results obtained with the Energy- and DVH-based optimization schemes were studied through commonly used dosimetric indices (DIs). Statistical equivalence tests were further performed to establish population-based significance results. Results: Both DVH- and Energy-based plans for each case were normalized so that 95% of the PTV receives the prescription dose. The average differences for the rectum and bladder DIs ranged from 1.6% to 25%, where the Energy-based quantities were lower. For both femoral heads the Energy-based optimization derived doses were lower on average by 32%. The statistical tests demonstrated that the significant differences in the tallied dose indices range from 2.7% to more than 50% for rectum, bladder and femoral heads. Conclusions: For majority of the clinically relevant dosiemtric quantities Energy-based inverse optimization performs better than the standard of care DVH-based optimization in prostate carcinoma. The population averaged statistically significant differences range from ~3% to ~50%. Therefore, this newly proposed optimization approach, incorporating explicitly quantitative imaging information in the inverse optimization function, holds potential for further reduction of complication rates in prostate cancer.